2013
DOI: 10.5946/ce.2013.46.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Cronkhite-Canada Syndrome Associated with Serrated Adenoma and Malignant Polyp: A Case Report and a Literature Review of 13 Cronkhite-Canada Syndrome Cases in Korea

Abstract: Cronkhite-Canada syndrome (CCS) is a rare nonfamilial polyposis syndrome characterized by epithelial disturbances both in the gastrointestinal tract and in the epidermis. The pathologic finding of the polyp is usually a hamartomatous polyp of the juvenile type; however, the possibility of serrated adenoma associated malignant neoplasm was reported in some Japanese cases. Up till now in South Korea, 13 CCS cases have been reported, but there was no case accompanied by the colon cancer. We report the first case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
1
24
0
1
Order By: Relevance
“…These changes often occur later during the disease progression, usually several weeks or months subsequent to the GI symptoms (8). Consistent with this, in the present case study, the patient initially experienced diarrhea and hematochezia, followed by abdominal pain, nail and toenail loss, onychatrophy and hyperpigmentation.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…These changes often occur later during the disease progression, usually several weeks or months subsequent to the GI symptoms (8). Consistent with this, in the present case study, the patient initially experienced diarrhea and hematochezia, followed by abdominal pain, nail and toenail loss, onychatrophy and hyperpigmentation.…”
Section: Discussionsupporting
confidence: 71%
“…CCS is a rare, acquired, nonhereditary syndrome with diffuse GI polyposis associated with ectodermal changes, including hyperpigmentation, alopecia and onychatrophy (8,9). Additionally, it has been reported that the CCS has been associated with poor prognosis and life-threatening malignant complications (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinomas of the colorectum (most often distal) and stomach have been documented in 15–25% of patients with CCS at diagnosis and may be multiple 5 26 76–92. Additionally, up to 40% of patients with CCS have been found to harbour colorectal adenomas and adenomatous change is sometimes seen in close proximity to CCS polyps and carcinoma 12 79 82 86 93–95.…”
Section: Risk For Gi and Other Neoplasmsmentioning
confidence: 99%
“…The index patient was a 68-year-old male with characteristic manifestations. Yun et al, reported a case of CCS in a 72-year-old male patient who presented with diarrhoea and weight loss along with both hand and feet nail dystrophy, hyperpigmentation, and alopecia [7]. Kao et al, mentioned a case of a 39-year-old Filipino woman who initially presented with diarrhoea but later developed significant amount of hair loss as well as hyperpigmentation of her palms and soles [8].…”
mentioning
confidence: 99%